EVALUASI PEMASANGAN DAN PEMELIHARAAN ALAT PEMADAM API RINGAN DI GRESIK - Rizki Prasetya Wardana (The Indonesian Journal of Occupational Safety and Health, 2018)
Oil and gas industry is an industry sector that has a high risk of fire. Fire is a potential hazard which can caused material loss, break of the production process and the danger to the human life safety. The aim of this research is to evaluate the installation and maintenance of portable fire extinguisher in PT. Pertamina Lubricants Production Unit Gresik. This research was observational and descriptive research using cross sectional design. The data used are primary data obtained from observations and interviews, and secondary data from documents and other supporting reports. The result showed that management has provided portable fire extinguisher almost every corner of the office building and production areas. The results of the identification of a potential fire hazard in PT. Pertamina Lubricants Production Unit Gresik that there is a potential fire hazard group A (solid materials, except metal), group B (material flammable liquid or gas) and group C (voltage electrical installations). Variables which have been in accordance with Decree of Minister of Labor No.04/MEN/1980 is the type and condition, within the installation, and the suitability of portable fire extinguisher signs, while variable that does not fit is the mounting height, sign mounting height and maintenance of portable fire extinguisher. The conclusion is PT. Pertamina Lubricants Production Gresik Unit has carried out the installation and maintenance of portable fire extinguishers but some are not in accordance with the regulations.Keywords: fire, installation, maintenance, portable fire extinguisher